A Descriptive Study On Morbidities Of Patients Attending Free Health Camp In Sankhejung Vdc Of Ilam District, Nepal - Rayamajhi, Rajan Bikram; Yadav, DK; Ghimire, A; Khanal, VK; Tamrakar, D; Shrestha, A; Shrestha, G; Sharma, M; Manandhar, N; Bhattachan, M; Gautam, R; Pokharel, PK (Journal of Chitwan Medical College, 2014)
Free health camp is an important means to cater health services to the needy people in an underdeveloped country like Nepal with difficult geographical terrain. The objective of this study was to assess the morbidities of patients attending the free health camp in Sankhejung, Ilam. A total of 399 patients visited the health camp and 35.1% of them were males. It was observed that diseases with musculoskeletal system and gastrointestinal system were reported among 24.3% and 25.1% of the attendees respectively. Based on the findings, it was concluded that the free health camp services was utilized more by the females and more burden of disease was found among musculoskeletal and digestive system. Journal of Chitwan Medical College 2013; 3(4); 48-51 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9555